Analisis Terpaan Iklan Partai Politik Di Televisi Pada Pemilih Pemula Di Kota Denpasar Dalam Pemilu Legislatif 2014 - Kertayasa, I Putu Agus Nanda; Gelgel, Ni Made Ras Amanda; Pradipta, Ade Devia (E-Jurnal Medium, 2017)
ABSTRACT Election on 2014 was a battle between politicians. Almost every politicians campaigning for themselves or their party to gain people’s vote. On the campaign period, we see a lot of political party’s campaign on television. Analysis shows that 62.3% beginner voters frequently exposed by political party commercial on television, but not all of them watch the whole commercial. 40.8% of the respondent did not watch the whole commercial from start to end. Even though the PDI Perjuangan commercial was the most viewed and interesting, it doesn’t make it the most remembered and liked commercial. Gerindra’s commercial was the most remembered and liked by the viewers. It was because of the commercial presents a politician with high popularity, it was PrabowoSubianto. Even though beginner voters’ perception to political commercial is on positive state and the exposure intensity is high, it doesn’t make voters choose those political party. Beginner voters tend to see more of the politician figure to choose. Keyword: commercial Exposure, beginner voters, political party commercial